2007
DOI: 10.1090/s0077-1554-07-00163-x
|View full text |Cite
|
Sign up to set email alerts
|

On the convergence of Padé approximations for generalized Nevanlinna functions

Abstract: We study a stepwise algorithm for solving the indefinite truncated moment problem and obtain the factorization of the matrix describing the solution of this problem into elementary factors. We consider the generalized Jacobi matrix corresponding to Magnus' continuous P -fraction that appears in this algorithm and the polynomials of the first and second kind that are solutions of the corresponding difference equation. Weyl functions and the resolution matrices for finite and infinite Jacobi matrices are compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 36 publications
0
64
0
Order By: Relevance
“…It can be shown that any Θ ∈ U z1 can be written as a minimal product of elementary factors; see [2] and [20] for the case z 1 = ∞.…”
Section: Theorem 74mentioning
confidence: 99%
“…It can be shown that any Θ ∈ U z1 can be written as a minimal product of elementary factors; see [2] and [20] for the case z 1 = ∞.…”
Section: Theorem 74mentioning
confidence: 99%
“…Unlike the classical case, we see that for a finite number of values z ∈ D, the limit in (3.9) is zero. Indeed, if z 0 ∈ C \ R is an eigenvalue of H (and hence a singularity of the m-function; see [5,6] [16,Theorem 13.3.1] here). Then, if z ∈ D is such that z + 1/z = z 0 , then the limit in (3.9) is zero.…”
Section: Theorem 33 (Geronimus Relations)mentioning
confidence: 99%
“…Then, if we consider the bilinear form on ℓ 2 (x, y) G = (Gx, y) ℓ2 , x, y ∈ ℓ 2 , we see that (Hx, y) G = (x, Hy) G . Next, following [9] and [10] we can also introduce the m-function of H via the formula m(z) = ((H − z) −1 e, e) G , e = (1, 0, 0, . .…”
Section: The Underlying Jacobi Matricesmentioning
confidence: 99%